Correlation between pancreatic cancer and metabolic syndrome: A systematic review and meta-analysis - Zhong, Lei; Liu, Jifeng; Liu, Shuo; Tan, Guang (Frontiers in Endocrinology, 2023)
Objective Pancreatic cancer is a globally frequent cause of death, which can be caused by many factors. This meta-analysis was performed to assess the correlation between pancreatic cancer and metabolic syndrome (MetS). Methods Publications were identified by searching PubMed, EMBASE, and the Cochrane Library for studies published until November 2022. Case-control and cohort studies published in English that provided information on the odds ratio (OR), relative risk (RR), or hazard ratio (HR) of metabolic syndrome and pancreatic cancer were included in the meta-analysis. Two researchers separately retrieved the core data from the included Random effects meta-analysis was conducted to summarize the findings. Results were presented as relative risk (RR) and 95% confidence interval (CI). Results MetS showed a strong association with an increased risk of developing pancreatic cancer (RR1.34, 95% CI1.23–1.46, P<0.001), and gender differences were also observed (men: RR 1.26, 95% CI 1.03–1.54, P=0.022; women: RR 1.64, 95% CI 1.41–1.90, P< 0.001). Moreover, an increased risk of developing pancreatic cancer was strongly linked to hypertension, poor high-density lipoprotein cholesterol, and hyperglycemia (hypertension: RR 1.10 CI 1.01–1.19, P=0.027; low high-density lipoprotein cholesterol: RR 1.24 CI 1.11–1.38, P<0.001; hyperglycemia: RR 1.55, CI 1.42–1.70, P< 0.001). However, pancreatic cancer was independent of obesity and hypertriglyceridemia (obesity: RR 1.13 CI 0.96–1.32, P=0.151, hypertriglyceridemia: RR 0.96, CI 0.87–1.07, P=0.486). Conclusions Although further prospective studies are required for confirmation, this meta-analysis indicated a strong relationship between MetS and pancreatic cancer. Regardless of gender, a greater risk of pancreatic cancer existed in people with MetS. Patients with MetS were more likely to develop pancreatic cancer, regardless of gender. Hypertension, hyperglycemia, and low HDL-c levels may largely account for this association. Further, the prevalence of pancreatic cancer was independent of obesity and hypertriglyceridemia. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022368980.